Steroid Injections Versus Autologous Blood Injections: Treatment Analysis in Plantar Fasciitis Patients: A Randomized Controlled Trial - Nisar Ahmed Soomro, Rasheed Ahmed Bhatti, Sijad Ahmed Mahar, Azizullah Bhayo, Hassan Amir Us Saqlain, Ali Muhammad Bhutto, Niaz Hussain Keerio (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the effectiveness of autologous blood injection versus steroid injection, in the treatment of Plantar Fasciitis. Study Design: A Randomized Controlled Trial Place and Duration: This study was conducted at Alhada Armed Forces Hospital Taif KSA from January 2021 to July 2021. Methodology: A total of 44 participants who had plantar fasciitis, for more than 6 weeks were divided into two groups. Group A was treated with autologous blood injections and the other group with steroid injections. Those patients with plantar fasciitis who were gone through certain surgical (heel surgery, ankle dislocation, rupture of plantar fascia, calcaneal fracture, tarsal bone fracture, and metatarsal bone fracture) procedures prior to having the disease were excluded from the study. Result: The total number of males in Group A and Group B were 23 and 19 respectively. The total number of females in Group A and Group B were 21 and 25 respectively. Treatment through autologous blood was effective in 26 patients of Group A and treatment through steroids was effective in 31 patients of Group B. Group A and Group B consisted of individuals that had average ages of 37 years and 38 years respectively. Conclusion: Autologous blood injections were not more effective than steroid injections in the treatment of plantar fasciitis.